Impact of Temperature on DC and AC Characteristics of Stacked Oxide SiO2/HfO2Cylindrical Gate Tunnel FETs - Singh P.K.; Baral K.; Kumar S.; Tripathy M.R.; Singh A.K.; Upadhyay R.K.; Jit S. (My University, 2025)
Based on three dimensional mathematical simulation, it has demonstrated that impression of temperature on the DC (i.e. $I_{d}, g_{m}, SS$, and $I_{\text{ON}}/I_{\text{OFF}}$ ratio) and AC (i.e. $C_{gg}, f_{t}$, and GBW) characteristics of stacked-oxide SiO2/HfO2 cylindrical gate (CG) tunnel field-effect transistors (TFETs). From the results of simulation, it is perceived that OFF-state current drastically changed for entire range of temperature (250K to 400K) while ON-state current is almost independent of temperature. Further, the effects of temperature on $C_{gg}, f_{t}$, and GBW shows that it is drastically changed at higher $V_{\text{gs}}$ while almost constant with lower $V_{\text{gs}}(V_{\text{gs}} < 0.5\mathrm{V})$. © 2020 IEEE.